(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
Since Constitutional Amendment 45 - which introduced the binding precedent into our system - some legal scholars have reiterated the need to establish a theory for the application of precedents in Brazil. The aim of this article is to demonstrate that a post-positivist hermeneutic understanding of the legal phenomenon is necessary in order to ensure an integral, coherent and constitutionally appropriate application of the binding provisions listed in art. 927 of the NCPC. Failure to understand a hermeneutic critique of the law could lead one to believe that the right thing to do is to structure a theory of the application of precedents in Brazil. This misunderstanding can lead to a regression to a primitive model of positivism, in which the text is equated with the norm which, in turn, has an abstract and non-concrete nature, as if it were possible for a binding decision to contain in itself a ready-made solution for future cases. The purpose of this article is precisely to avoid these risks and to provide minimum theoretical elements for a constitutionally appropriate application of the binding rulings contained in the NCPC.